A daily diary approach to investigate the effect of ego depletion on intentions and next day behavior. (November 2018) - Rebar, Amanda L.; Dimmock, James A.; Rhodes, Ryan E.; Jackson, Ben
Abstract: Objectives: Ego depletion impairs physical and cognitive capacities, but its effects on daily intentions and behavior remain unclear. This study provides insight into relationships between ego depletion, intentions, and exercise, leisure sitting and other non-activity related behaviors. Design: The study involved repeated assessment using a daily diary. Method: Australian university students ( N  = 103, 52% female, M age = 22 years) self-reported end-of-day ego depletion, decisional intentions, and behavior for time spent exercising, in leisure-time sitting, doing paid work, sleeping, studying, housework, and the amount of alcohol consumed across seven days. Results: When people were more ego depleted at the time of reporting intentions, they intended to exercise for less time the next day than when people were less ego depleted. However, if people were highly ego depleted when reporting exercise intentions for the next day, they were subsequently more likely to reach those intentions. There were no significant effects of ego depletion on intentions or on the likelihood of achieving intentions for any behavior other than exercise. Conclusions: Given that the effects of ego depletion on intentions and behavior were seen for exercise but not other daily behaviors, it may be that ego depletion only impacts intentions to engage in physically effortful behavior. Future research is needed to test replicability of the effects. Interventions may consider accounting for ego depletion in efforts to enhance behavioral intentions; however, the findings also highlight the importance of keeping behavior change (as opposed to change in intentions) as the main outcome focus. Highlights: Being ego depleted when making plans for exercise results in more modest plans. The negative effects of ego depletion on plans does not necessarily impact behavior. Being ego depleted when making plans does not impact intentions for other behaviors. It may be that ego depletion reduces only intended time spent in effortful activity. Behavior change efforts need to focus on behavior as the outcome rather than plans.